2018
DOI: 10.14203/ann.bogor.2018.v22.n2.65-74
|View full text |Cite
|
Sign up to set email alerts
|

DNA Condensation Study of Fully Synthesized Lipopeptide-Based Transfection Agent for Gene Delivery Vehicle

Abstract: The main requirement of transfection agent has to condense DNA in nanoparticle size, protect the DNA from nucleases and other degrading enzymes during its transport in cell cytoplasm and nucleus and should not toxic to target cells. In this research, lipopeptide composed of palmitoyl (C-16) and short peptide sequence have been designed fully synthesized and tested to DNA condensation capability and toxicity. The DNA condensation study was performed using EtBr exclusion assay and cytotoxicity determination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The MTT assay was carried out by detecting the enzymatic mitochondrial activity of live and healthy cells mediated by oxidoreductase and dehydrogenases [19,38,39]. It was found that the liposome composed of cholesterol: DPPC: DSPE-PEG2000 (9.5:9.5:1) is relatively non-toxic to the cells, since up to 1600 µg/mL, the cell viability was more than 80% compared to the control (data are not shown).…”
Section: Biological Activity Of the Liposome-based Adjuvantmentioning
confidence: 99%
“…The MTT assay was carried out by detecting the enzymatic mitochondrial activity of live and healthy cells mediated by oxidoreductase and dehydrogenases [19,38,39]. It was found that the liposome composed of cholesterol: DPPC: DSPE-PEG2000 (9.5:9.5:1) is relatively non-toxic to the cells, since up to 1600 µg/mL, the cell viability was more than 80% compared to the control (data are not shown).…”
Section: Biological Activity Of the Liposome-based Adjuvantmentioning
confidence: 99%